Building Personal Integrity and Positive Character toward an Outstanding Generation. - Elvie Maria; Amril Amril; Andriasan Sudarso; Lili Suryati (Jurnal Abdisci, 2026)
This Community Service Program (PKM) aims to enhance young people's understanding of the importance of personal integrity and positive character as fundamental pillars in developing an outstanding generation in the modern era. Challenges in the VUCA era (Volatility, Uncertainty, Complexity, and Ambiguity) require young people not only to possess intellectual intelligence but also strong character, adaptability, responsibility, and sound social ethics. The program was implemented through educational seminars, material presentations, interactive discussions, and participant reflections. The topics covered included personal integrity, positive character development, challenges in the digital era, soft skills development, and the role of young people as agents of change. The results indicated an increased understanding among participants regarding the importance of integrity, discipline, responsibility, empathy, teamwork, and critical thinking as essential characteristics of an outstanding generation. Participants also demonstrated high enthusiasm during discussions and a strong commitment to applying positive values in their daily lives. This program contributed positively to raising awareness that success is determined not only by academic competence but also by the quality of character and personal integrity as important assets for national developme